Design of Storage Warehouse with Environmentally Friendly Concept: Case Study of ABC Fuel Terminal - Pratama, Ibnu Lukman; Baharrudin, Rafief (Jurnal Rekayasa Kimia & Lingkungan, 2025)
This article presents the design of a storage warehouse at the ABC fuel terminal using an environmentally friendly approach. The concept integrates renewable energy, sustainable building design, ventilation systems, natural lighting, automation, and efficient layout arrangements. A quantitative method is applied to calculate the site area systematically based on field conditions. The total design area is 467.26 m, with dimensions of 30.5 m in length and 15.32 m in width. To minimize environmental impact, the warehouse design incorporates several sustainable features. Solar panels serve as a renewable energy source to reduce reliance on conventional electricity. A transparent polycarbonate roof allows natural daylight to illuminate the interior, reducing the need for artificial lighting during the day. Rotary ventilation systems enhance air circulation, decreasing the dependency on air conditioning and promoting a comfortable working environment. Environmentally friendly Material Handling Equipment (MHE), such as electric or alternative-fuel forklifts, is proposed to lower emissions and energy use. Furthermore, the application of the 3R (Reduce, Reuse, Recycle) principles ensures minimal waste generation, efficient resource usage, and the reuse of viable materials. The warehouse layout adopts a specialized storage system that significantly improves the efficiency of item search, placement, and retrieval. Together, these strategies contribute to a sustainable and efficient warehouse design.